Efforts to Prevent Tuberculosis Transmission Based on the Health Belief Model Theory in West Lombok - Agus Supinganto; Ina Kusrini; Asih Setyarini; Lili Amaliah; Selasih Putri Isnawati Hadi; Irwan Budiana (Universitas STRADA Indonesia, 2020)
The community's high incidence of tuberculosis is closely related to behaviour, and family involvement. Transmission preventance becomes an important factor in controlling transmission of tuberculosis. The purpose of this study is to identify efforts to prevent tuberculosis transmission in western Lombok. Method. concise exploratory design using cross-sectional sampling of the sample using a purposeful sampling process with 58 respondents. Result. 72 % of respondents took measures to prevent tuberculosis based on the health belief model, namely; perceived susceptibility 72%; perceived seriousness 78%; perceived benefits 81%; perceived barriers 67%; and cues to action 65%. Duscussion.The need to improve family members' awareness about tuberculosis prevention and to practice safe and healthy living activities at all times.